2023
DOI: 10.1109/access.2023.3249108
|View full text |Cite
|
Sign up to set email alerts
|

Solar PV Power Estimation and Upscaling Forecast Using Different Artificial Neural Networks Types: Assessment, Validation, and Comparison

Abstract: His research interests include digital signal processing for communications, multimedia, image, and video coding, low-power wireless communications, one-bit ADC multiple-input multiple-output, underwater communication, index and spatial modulation, Li-Fi technology, and visible light communication. He is a Technical Committee Member of many international conferences and a Reviewer of many international conferences, journals, and transactions. Moreover, he was the General Co-Chair of the IEEE ITCE, in 2018. Moh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…To fulfil the obligations of the ADNs and overcome the drawbacks of the previous approaches (model-based approaches), the applications of AI algorithms are extensively applied in MPSs [214]. Hence, the data-driven approaches are utilized to process the historical dataset or measured data from smart meters, to develop models for real-time estimation and forecasting of the HC of the ADNs with reliable operation [10].…”
Section: Datadriven Approachesmentioning
confidence: 99%
“…To fulfil the obligations of the ADNs and overcome the drawbacks of the previous approaches (model-based approaches), the applications of AI algorithms are extensively applied in MPSs [214]. Hence, the data-driven approaches are utilized to process the historical dataset or measured data from smart meters, to develop models for real-time estimation and forecasting of the HC of the ADNs with reliable operation [10].…”
Section: Datadriven Approachesmentioning
confidence: 99%
“…The suggested NN types were contrasted with other relevant earlier methods that are discussed in references [7,[58][59][60]. This comparison aimed to clarify the influence of the NN in estimating output power under different conditions.…”
Section: Comparison With Earlier Researchsmentioning
confidence: 99%
“…This indicated that employing our suggested structures improved both the accuracy and the closeness between estimated and true power. While it was not stated and was not explored with others, the generalization ability under various scenarios and conditions was evaluated with our suggested approach by Abdel-Nasser, et al [7]. Figure 15 shows the difference between suggested methods and the other approaches mentioned in Table 10 by displaying the accuracy percentage (%) that could be calculated by the difference between 100 and MSE% (100-MSE%).…”
Section: Comparison With Earlier Researchsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is used for scheduling day-ahead balancing between supply and demand associated with energy markets [83,84]. • Long-medium term (weekly or seasonal): it refers to the ability of power systems to respond to changes in demand and supply within a week or over a season which can be used in hydro units, thermal units or RESs scheduling [85,86]. • Long term (years): for planning the power system generation and consumption for years regarding the energy costs, a longterm timescale is applied [87,88].…”
Section: Flexibility Timescalesmentioning
confidence: 99%